The Influence of Work Life Balance and Job Satisfaction on Employee Retention PT Complete Selular - Nur Aini Meiliza Fadilah; Bachrudin Syahroni; Moh. Yudi Mahadianto (BIP's JURNAL BISNIS PERSPEKTIF, 2026)
This study aims to analyze the effect of work-life balance and job satisfaction on employee retention at PT Complete Selular, in response to the increasing concern of employee turnover and the need to identify key factors influencing employees’ intention to remain in the organization. This research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected from 110 employees who meet the predetermined criteria. The results reveal that both work-life balance and job satisfaction have a significant effect on employee retention, with a high explanatory power indicated by an R-square value of 0.891, suggesting that 89.1% of the variance in employee retention is explained by the model. Specifically, work-life balance has a positive and significant effect (β = 0.313; p < 0.05), indicating that employees who are able to balance their professional and personal lives tend to have a higher intention to stay. Meanwhile, job satisfaction demonstrates a stronger and highly significant influence (β = 0.643; p < 0.001), making it the dominant factor affecting retention. These findings suggest that while work-life balance contributes to improving employees’ psychological well-being, job satisfaction plays a more critical role in determining retention decisions. Therefore, organizations are encouraged to adopt an integrated strategy by enhancing job satisfaction through supportive work environments, fair compensation, and effective management practices, while simultaneously maintaining work-life balance initiatives. This study contributes to the literature by providing empirical evidence from the Indonesian telecommunication distribution sector and offers practical implications for improving employee retention in similar organizational contexts.